[PP.27.11] 24 HOUR ARTERIAL DISTENSIBILITY IS RELATED WITH ABPM NON-DIPPING PATTERN IN HIV-POSITIVE PATIENTS. (September 2016) - Varrenti, M.; Maloberti, A.; Vallerio, P.; Panzeri, F.; Pessina, L.; Casadei, F.; Lucente, D.; D'Alessio, I.; Mondellini, G.M.; Motta, D.; Moioli, C.; Parati, G.; et al.
Abstract : Objective: The use of Anti-Retroviral Therapy (ART) has decreased AIDS–related mortality. However, ART treated HIV-patients have higher cardiovascular (CV) morbidity and mortality than general population. Although hypertension is a frequent risk factor in HIV-patients (both due to HIV inflammatory activation and ART drugs), existing data on Ambulatory Blood Pressure Monitoring (ABPM) phenotypes in this setting are limited, but suggest an increased prevalence of a non-dipping Blood Pressure (BP) pattern. The present study is aimed at determining the prevalence of non-dipping pattern in a population of unselected HIV-patients and it's association with arterial stiffness over 24 hour. Design and method: We studied 40 patients (72% man; 53.4 ± 8.8years). We measured office and 24 hour systolic (S) and diastolic (D) BP, the QKd interval during the ABPM evaluation (Dyasis Integra-Novacor, France). QKd represents an index of arterial stiffness and is calculated as the time (measured in ms) between the onset of the depolarization on the electrocardiogram (Q) and the detection of the last Korotkoff sound (K) during cuff deflation. We also obtained information on blood glucose and lipid values. Results: Our HIV positive patients showed normal mean office (127.8/76.5 ± 16.1/7.1 mmHg) and 24 h ABPM (121.1/79.8 ± 13.1/10.7 mmHg) BP values. Regarding CV risk factors 30% of them were smokers, 25% took antihypertensive and 17.5% lipid-lowering drugs. Seventeen patients (42.5%) showed non-dipping pattern at ABPM. Non-dipping patients were superimposable for age, office BP, 24 h and day ABPM, glucose and lipids values and HIV characteristics (infection time, ART time and drugs) to normal dipping patients. On the contrary, they showed a lower QKD (219.9 ± 22.8 vs 203.7 ± 21.3 ms for dippers and non-dippers respectively, p = 0.02). QKd correlates with age (r = −0.57, p < 0.001), 24hDBP (r = 0.32, p = 0.04) and glucose (r = −0.36, p = 0.03) but not with HIV charactheristics and CV risk factors. The independent predictors of QKd at multivariate analysis were age (β = 0.54, p = 0.001) and 24hDBP (β = 0.34, p = 0.01). Conclusions: Our results suggest that non-dipping BP is a frequent pattern in HIV-patients and is associated with impairment of arterial distensibility. Nor HIV-infection status parameters nor ART seems to be directly responsible for non-dipping pattern; on the contrary age and 24 hour DBP seem to be strictly related both with dipping and distensibility.